Walking the walk : having your customers love you - Brunner, Robert, 1958- (FTPress Delivers elements., 2010)
This Element is an excerpt from Do You Matter?: How Great Design Will Make People Love Your Company (ISBN: 9780137142446) by Robert Brunner and Stewart Emery. Available in print and digital formats. A process, not an event: achieving total commitment to building a design-driven company, from top to bottom. Even companies that get on the path of being design driven may have rogue cells in their DNA that can multiply to become a potentially fatal flaw. The risk is almost always around losing the magic that got them where they were, backing away from a living approach that ensured freshness and ongoing vision....